1981
DOI: 10.1111/j.1469-7998.1981.tb03435.x
|View full text |Cite
|
Sign up to set email alerts
|

Optomotor responses of three congeneric gekkonid lizards having different daily activity times*

Abstract: Optomotor responses of three Israeli forms of Ptyodactylus hasselquistii, exhibiting differences in daily activity patterns, were studied. The number of reorientation movements was affected by drum velocity, stripe width and light intensity. The three closely related forms responded differently in correlation to their time of daily activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…(1995). Similarly, Frankenberg (1981) showed interspecific differences in optomotor response in geckos that are active at different times of the day. Motion sensitivity that is environmentally tuned may be common in many terrestrial taxa (e.g.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…(1995). Similarly, Frankenberg (1981) showed interspecific differences in optomotor response in geckos that are active at different times of the day. Motion sensitivity that is environmentally tuned may be common in many terrestrial taxa (e.g.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, the retinal outer segments of the diurnal Sphaerodactylus are relatively smaller in size than those of nocturnal geckos, thus limiting Sphaerodactylus visual sensitivity under low light levels (Roll 2000). In a study comparing motion detection between geckos with different activity times (diurnal, nocturnal, crespusular), Frankenberg (1981) found that the diurnal geckos did better under high light intensities. However, our results suggest that despite retinal adaptations to a diurnal lifestyle, Sphaerodactylus from bright and dark environments are still better able to detect motion in relatively dim light.…”
Section: Discussionmentioning
confidence: 99%